Evaluation of the Implementation of the Setoran Mutun Thalabil 'Ilmi Program in Improving the Quality of Madrasah Education - Rizka Dwi Oktaviani; Mohammad Zakki Azani; Hakimuddin Salim (Institut Agama Islam An-Nawawi Purworejo, 2025)
Islamic education in Indonesia, particularly in Islamic schools (madrasahs), faces significant challenges in improving the quality of learning and strengthening the character of students in the era of globalization. One innovation emerging to address this challenge is the Setoran Mutun Thalabil 'Ilmi (Information and Learning) program implemented at the Islamic Senior High School (Islamic Boarding School) PPMI Assalaam. This program combines traditional Islamic boarding school methods with digital technology to improve educational quality. This study aims to evaluate the implementation of the Setoran Mutun Thalabil 'Ilmi program among female students in the top class at the Islamic Senior High School (Islamic Boarding School) PPMI Assalaam in an effort to improve the quality of madrasah education. The method used in this study was a qualitative case study approach. Data were collected through interviews, observations, and documentation studies, and analyzed descriptively. The main findings of this study indicate that the Setoran Mutun Thalabil 'Ilmi program has a positive impact on educational quality, both in terms of process and outcomes. The learning process, which combines online and face-to-face methods, improves the discipline, motivation, and independence of female students, while the results are seen in improved Arabic language skills and a deeper understanding of Islam. Significant supporting factors include institutional support, madrasah policies, and the competence of the supervising teachers. The conclusion of this study is that the program successfully integrated Islamic boarding school traditions with modern technology, contributing to improving the quality of madrasah education. This study also suggests that other madrasahs can adopt a similar approach to improve the quality of learning in the digital age. Future research is recommended to examine the program's impact on academic achievement in greater depth quantitatively.